Energy Efficient Refurbishment of Old Listed Dwellings: The Case of Victorian Housing Stock - Makrodimitri, Magdalini (Consilience, 2010)
Architecture has to contribute to climate change recovering, by designing in a more responsible way respecting nature, local climatic, cultural, social and economic conditions, using the inexhaustible energy of the sun, wind, earth and water as Renewable energy Resources and existing local materials and resources as well. Making buildings more sustainable to time and space means that we also have to respect cultural heritage, the past, the present and the future. Architecture has also to ensure thermal comfort and healthy indoor environment during the whole year, while diminish conventional fuels consumption on the base of bioclimatic, energy efficient approach. Buildings in use or in course of erection account for over 50% of total greenhouse gas emissions. Consequently, upgrading old inefficient buildings so as to meet principles of bioclimatic design is an effective way to reduce energy use in industrialized countries. (Smith, 2005) However, refurbishment schemes should include both environmental design and conservation of architectural, historical and social values of old existing stock. This paper consists of two parts. At first there is a review of the objectives, targets and studies regarding the old existing UK housing stock, in order to highlight the principles and advantages of bioclimatic design and energy efficient improvements to listed buildings’ fabric and services. The second part contains an evaluation of performance of the recently refurbished 17 St Augustine’s road Victorian House in London. Critical assessment of its current performance has been carried out according to winter and summer on site measurements, simulations and calculations in TAS and SAP softwares. This study will be focuses more on winter performance and annual heating fuel demands. Occupants’ behaviour and its impact on Low Energy Victorian Dwelling’s (LEVH) performance has also been investigated through a questionnaire survey, while the cost of refurbishment scheme is evaluated in terms of positive effectiveness to annual savings.